2009
DOI: 10.1128/mcb.01454-08
|View full text |Cite
|
Sign up to set email alerts
|

A Class III PDZ Binding Motif in the Myotilin and FATZ Families Binds Enigma Family Proteins: a Common Link for Z-Disc Myopathies

Abstract: Interactions between Z-disc proteins regulate muscle functions and disruption of these interactions results in muscle disorders. Mutations in Z-disc components myotilin, ZASP/Cypher, and FATZ-2 (calsarcin-1/ myozenin-2) are associated with myopathies. We report here that the myotilin and the FATZ (calsarcin/ myozenin) families share high homology at their final C-terminal five amino acids. ThisL motif is present almost exclusively in these families and is evolutionary conserved. We show by in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 57 publications
2
96
0
1
Order By: Relevance
“…This suggests that the protein that binds to the PDZ domain of CLP36 has a critical role in neurite outgrowth. Recently, it has been shown that palladin binds to the PDZ domain of ALP/Enigma family proteins (von Nandelstadh et al 2009). Palladin is an actin cross-linking protein and interacts with Ena/VASP and profilin which regulate actin polymerization (Goicoechea et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the protein that binds to the PDZ domain of CLP36 has a critical role in neurite outgrowth. Recently, it has been shown that palladin binds to the PDZ domain of ALP/Enigma family proteins (von Nandelstadh et al 2009). Palladin is an actin cross-linking protein and interacts with Ena/VASP and profilin which regulate actin polymerization (Goicoechea et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ALP/Enigma proteins interact with ABPs such as aactinin (Xia et al 1997;Zhou et al 1999;Nakagawa et al 2000;Torrado et al 2004;Vallenius et al 2004), b-tropomyosin (Guy et al 1999), and palladin (von Nandelstadh et al 2009), and through these interactions ALP/Enigma proteins are thought to participate in the organization and regulation of cytoarchitecture. The members of this family has one amino-terminal PDZ domain and one carboxyterminal LIM domain [CLP36, Mystique, ALP, and Reversion-induced LIM protein (RIL)] or a single amino-terminal PDZ domain and three carboxy-terminal LIM domains [enigma homologue protein (ENH), ZASP/Cypher, Enigma].…”
mentioning
confidence: 99%
“…Again, at least five of the 10 known PDZ-LIM pro-teins localize to the z-disc (including Enigma, ENH, Cypher/ ZASP/Oracle, CLP36, and ALP). Recently, van Nandelstadh et al (16) proposed a new PDZ type III domain in proteins of the myotilin family (including myotilin, palladin, and myopalladin) and the calsarcin/FATZ/myozenin family that mediates the interaction of both families with proteins of the Enigma family.…”
Section: Molecular Architecture Of Z-disc Proteinsmentioning
confidence: 99%
“…The serine rich domain consists of a stretch of hydrophobic residues that are believed to direct the localisation of Myotilin to the sarcolemma [10]. The serine rich domain is also responsible for the interaction of Myotilin with a range of proteins including the primary Z-disk crosslinker -Actinin [153], Filamin-Actin-and Telethonin-binding protein of the Z-disk (FATZ, Myozenin, Calsarcin) [157], ZASP/Cypher [158], Filamin C [157,159] and the ubiquitin ligases MURF-1 and MURF-2 [160]. Interaction of Myotilin with FATZ directly or indirectly directs the localisation of FATZ to the Z-disk [157].…”
Section: Myotilin and Myotilinopathiesmentioning
confidence: 99%
“…ZASP contains a PDZ domain, located at the N-terminus, and an internal ZASP/cypher-like motif (ZM) both capable of interacting with -Actinin-2 [179][180][181]. Additionally, the PDZ domain interacts with Myotilin [158] and FATZ [182], which provides structural stability to the Z-disk. The Cterminus contains three LIM domains, which act to recruit signalling proteins to the Z-disk.…”
Section: Zasp and Zaspopathiesmentioning
confidence: 99%